2014
DOI: 10.17988/0198-7429-40.1.15
|View full text |Cite
|
Sign up to set email alerts
|

SRSD in Practice: Creating a Professional Development Experience for Teachers to Meet the Writing Needs of Students with EBD

Abstract: Self-regulated strategy development (SRSD) is one of the most effective writing interventions (Graham, McKeown, Kiuhara, & Harris, 2012) and has improved the writing skills of students with emotional and behavior disorders (EBD). Practice-based professional development (PBPD) has been effective for teaching participants how to implement SRSD with fidelity. Through a review of prior studies, analysis of a small qualitative sample, and reflection on anecdotal notes from recent PBPD implementations, suggestions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Graham and Perin (2007) noted that SRSD significantly improves the structure of the writing of students in Grades 4 through 12 when compared with other types of strategy instruction and control conditions. Similar findings were noted in Mason and Graham's (2008) review of writing instruction for Grade 4 through 12 students with learning disabilities; SRSD instruction resulted in large gains in writing quality when compared with that of students in a business-as-usual control group (ES = 1.26-1.35) and in a separate review documenting improved writing skills for students with emotional and behavioral disorders (McKeown, Fitzpatrick, & Sandmel, 2014).…”
Section: Self-regulated Strategy Development (Srsd)supporting
confidence: 73%
“…Graham and Perin (2007) noted that SRSD significantly improves the structure of the writing of students in Grades 4 through 12 when compared with other types of strategy instruction and control conditions. Similar findings were noted in Mason and Graham's (2008) review of writing instruction for Grade 4 through 12 students with learning disabilities; SRSD instruction resulted in large gains in writing quality when compared with that of students in a business-as-usual control group (ES = 1.26-1.35) and in a separate review documenting improved writing skills for students with emotional and behavioral disorders (McKeown, Fitzpatrick, & Sandmel, 2014).…”
Section: Self-regulated Strategy Development (Srsd)supporting
confidence: 73%
“…To guide instruction and feedback, teachers should develop, choose, or adapt a rubric or checklist for the genre so expectations are clearly established (McKeown et al, 2014, 2020). The rubric or checklist will be used to measure student writing, to guide teacher audio feedback, and for student self-assessment.…”
Section: Getting Started: Writing Prompts and Measuresmentioning
confidence: 99%
“…When offering feedback to elementary students, teachers frequently focus on surface features, such as grammar, spelling, punctuation, or phrasing, which improves neither content nor organization (Matsumara et al, 2000, 2002). Curriculum, testing, and administrative demands in modern classrooms may limit instruction and preparation time contributing to this lack of rich feedback (McKeown et al, 2014). Teachers may find writing detailed comments laborious and time-intensive.…”
mentioning
confidence: 99%
“…The SRSD model of instruction holds appeal for researchers and teachers who are interested in finding ways to improve students’ writing outcomes. To date, researchers have documented that practice-based professional development (PBPD) serves as an effective way to support special education teachers in implementing SRSD writing instruction with high levels of fidelity (Gillespie Rouse, & Kiuhara, 2017; McKeown et al, 2014). Taking PBPD one step further, Cuenca-Carlino et al (2018) demonstrated that a bilingual special education teacher was able to implement SRSD persuasive writing instruction with fidelity in a study where results also showed gains in the writing quality and quantity for nine ELLs in Grades 2 and 3 (including four ELLs with disabilities).…”
Section: Self-regulated Strategy Developmentmentioning
confidence: 99%